PENERAPAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEMATANG PUDU KECAMATAM MANDAU KABUPATEN BENGKALIS TAHUN PELAJARAN 2015/2016 - Sarpin, Sarpin; Antosa, Zariul; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Science is the study of living organisms and life processes in the universe and find out about the nature systematically. So that the IPA is not just a collection of knowledge mastery of facts, concepts or principles whatever. Problems were found in this study is less varied learning so that students are less interested in following science subjects so that the value obtained is not satisfactory. To solve these problems, the authors make improvements with the goal of learning to improve student learning outcomes in science subjects style material using inquiry methods. It can be seen from the data collected, it looks at first students received grades above KKM only 11 students. The results of student learning continues to increase in cycle 1 and cycle 2 only 2 students who have not reached the KKM. The percentage of completeness of students increased from 39.29% at baseline to 92.86% score on the improvement of the second cycle. So from the results it can be concluded that the application of the method of inquiry can improve student learning outcomes in science subjects of Style in class IV B SD Negeri 67 Pematang Pudu.Key Words: Inquiry, Learning Outcomes, IPA